2018
DOI: 10.1299/jamdsm.2018jamdsm0022
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of densification behaviors during powder compaction

Abstract: With the rapid development of manufacturing technology powder compaction has been a highly-developed forming technology for manufacturing net shape or near net shape parts with complex geometries and special mechanical performances. An experimental and numerical investigation was made to study the densification behaviors during powder compaction. A series of compaction tests were carried out. A numerical model using multi-particle finite element model (MPFEM) was presented for densification analysis, particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…It's slightly lower than our final relative density. Lei et al [24] investigated the density' characteristic of the gas atomized Fe powders in conventional powder compaction. They found that the final relative density is about 0.95 when the compression force is up to 40 kN.…”
Section: Characterization Of Packing Structurementioning
confidence: 99%
See 2 more Smart Citations
“…It's slightly lower than our final relative density. Lei et al [24] investigated the density' characteristic of the gas atomized Fe powders in conventional powder compaction. They found that the final relative density is about 0.95 when the compression force is up to 40 kN.…”
Section: Characterization Of Packing Structurementioning
confidence: 99%
“…Although the densification of powder is widely investigated by 3D, the 2D simulation also can be used to capture the densification of powder in a cross section and reveals the evolution of densification and mechanical characteristics [23,24]. Olsson et al [23] investigated the process of cold powder compaction by 2D DEM model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A. Lu et al [24] modeled the cold isostatic pressing (CIP) process of Al powders by using MPFEM to study the effects of initial packing structures on the packing densification. Yu Lei et al [25] used the MPFEM for densification analysis for three different initial packing structures (hexagonal, tetragonal, and random) and the numerical results were compared with experimental data. The simulation results of MPFEM for a random packing structure showed a good agreement with the experimental results and can give insight into the particle-level densification mechanism in physical compaction tests.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature evolution and densification behaviors have important influence on the powder compaction process (Yan et al, 2017, Lei et al, 2018. Moreover, sintering is an essential process for achieving necessary properties including higher mechanical strength, enhanced sintering densification, homogeneous density distribution and preferable alloying performance.…”
Section: Introductionmentioning
confidence: 99%